Performance and the Possible: Embodiment, Privilege, and the Politics of Teaching Writing - Lesley Erin Bartlett (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
An astute examination of the roles students often expect their teachers to assume prompts questions and challenges for those whose bodies do not correspond with those expectations.